X-CHIME enables combinatorial, inducible, lineage-specific and sequential knockout of genes in the immune system - LaFleur, Martin W.; Lemmen, Ashlyn M.; Streeter, Ivy S. L.; Nguyen, Thao H.; Milling, Lauren E.; Derosia, Nicole M.; Hoffman, Zachary M.; Gillis, Jacob E.; Tjokrosurjo, Qin; Markson, Samuel C.; Huang, Amy Y.; Anekal, Praju V.; et al. (Nature immunology, 2024)
Annotation of immunologic gene function in vivo typically requires the generation of knockout mice, which is time consuming and low throughput. We previously developed CHimeric IMmune Editing (CHIME), a CRISPR–Cas9 bone marrow delivery system for constitutive, ubiquitous deletion of single genes. Here we describe X-CHIME, four new CHIME-based systems for modular and rapid interrogation of gene function combinatorially (C-CHIME), inducibly (I-CHIME), lineage-specifically (L-CHIME) or sequentially (S-CHIME). We use C-CHIME and S-CHIME to assess the consequences of combined deletion of Ptpn1 and Ptpn2 , an embryonic lethal gene pair, in adult mice. We find that constitutive deletion of both PTPN1 and PTPN2 leads to bone marrow hypoplasia and lethality, while inducible deletion after immune development leads to enteritis and lethality. These findings demonstrate that X-CHIME can be used for rapid mechanistic evaluation of genes in distinct in vivo contexts and that PTPN1 and PTPN2 have some functional redundancy important for viability in adult mice. Sharpe and colleagues devise a conditional gene deletion model in mice for rapid sequential, combinatorial and lineage-specific interrogation of gene function in hematopoietic cells.